Absence of Evidence as The Evidence Of Absence: The Curious Case of Latent Infection Causing Ocular Tuberculosis - Basu, Soumyava (Frontiers in Ophthalmology, 2022)
Ocular tuberculosis (TB) is frequently considered as intraocular inflammation in the setting of latent TB, owing mainly to the absence of microbiological evidence of Mycobacterium tuberculosis in ocular fluid samples. Even though such lack of microbiological evidence, and of systemic signs of active TB disease, are suggestive of latent TB infection, molecular and rare histopathologic evidence of mycobacteria in the eye, and favourable response of ocular inflammation to anti-TB therapy point to the presence of active infection in ocular TB. Here, we discuss how intraocular inflammation in ocular TB is not merely an immunologic response to bacilli, but an active tuberculosis infection. We will discuss the reason for the frequent absence of microbiological evidence of TB in the eye in ocular TB and the diagnostic hierarchy to arrive at the diagnosis of this infectious uveitis entity.